A wideband low power merged balance-balun-LNA and I/Q-mixer. (January 2021) - Eskandari, R.; Ebrahimi, A.; Baghtash, H. Faraji
Abstract: This paper presents a low power wideband RF receiver front-end in CMOS 180 ​nm technology that operates between 0.3 and 4.7 ​GHz. The mixer has a quadrature current commutating gilbert cell configuration that utilizes a novel broadband noise-canceling balanced balun-LNA as the transconductance stage. The noise-canceling balun LNA utilizes an additional noise-reduction technique that enhances its performance noticeably. Both of the common gate and common source stages of balun LNA are matched by employing equal-sized transistors that are biased with the same currents and load resistances. This technique results in superior symmetry, enhanced noise, and linearity performance under reduced power consumption. Post-layout simulation results show that the implemented balun LNA-I/Q-mixer has a conversion gain of 14.05 ​dB. The second and third-order intermodulation intercept points are +42.13 dBm and +4.13 dBm, respectively. The double-sideband NF is 4.74 ​dB. The proposed structure consumes only 6.7 ​mW from a 1.8 ​V supply and occupies a 0.056 ​mm 2 chip area.